Respuesta :
Answer: [tex]-9.66[/tex]
Step-by-step explanation:
Here the given expression, [tex]-a + (-b)[/tex]
Where [tex]a = 6.05[/tex] and [tex]b =3.61[/tex]
By putting the given values of a and b in the given expression,
We get,
[tex]- 6.05 + ( -3.61)[/tex]
[tex]= -6.05 - 3.61[/tex]
[tex]= - (6.05 + 3.61)[/tex]
[tex]= - 9.66[/tex]
Answer:
−9.661
Step-by-step explanation:
Let's substitute \blueD{a = 6.05}a=6.05start color #11accd, a, equals, 6, point, 05, end color #11accd and \maroonD{b = 3.611}b=3.611start color #ca337c, b, equals, 3, point, 611, end color #ca337c into the expression.
\begin{aligned} &\phantom{=} -\blueD{a}+(-\maroonD{b}) \\\\ &= -\blueD{6.05}+\left(-\maroonD{3.611}\right) \end{aligned}
=−a+(−b)
=−6.05+(−3.611)
=−6.05−3.611